Dynamic changes in brain structure in patients with post-traumatic stress disorder after motor vehicle accident: A voxel-based morphometry-based follow-up study - Yang, Luodong; Li, Haohao; Meng, Yao; Shi, Yan; Ge, Anxin; Zhang, Guiqing; Liu, Chaomeng (Frontiers in Psychology, 2022)
Objectives To investigate the dynamic changes of emotional and memory-related brain regions in post-traumatic stress disorder (PTSD) patients and trauma-exposed subjects, who experienced motor vehicle accident (MVA). Materials and methods Functional Magnetic Resonance imaging (fMRI) and general data were collected from trauma victims who had experienced MVA within 2 days, and their social support and coping style were evaluated. The PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (PCL-5) is used for screening and diagnosis. Subsequently, 17 PTSD patients and 23 car accident trauma-exposed individuals completed a second fMRI scan at 2 months. Data were analyzed by using voxel-based morphometry (VBM) to examine the volume changes of relevant brain regions. Correlation analysis was used to assess the correlation between the regions of interest (ROIs) and the total scores on the clinical scales. Subsequently, the relationship between the total PCL-5 scores and the individual dimensions of the Simplified Coping Style Questionnaire (SCSQ) and the Social Support Rate Scale (SSRS) was studied. Results In comparison with the control group, the results showed a reduction in right SFG volume in the PTSD group at 2 months. Similarly, a comparison within the PTSD group revealed a reduction in the left STG volume at 2 months. Compared with the control group, PTSD patients showed a more negative coping style and worse performance in objective and subjective support. In addition, the total PCL-5 scores were negatively associated with positive coping, objective support, and subjective support. Conclusion The occurrence of PTSD may be related to reduced volume of the right SFG and left STG, and that patients with PTSD receive less social support and tend to cope in a negative manner in the face of stressful events. These results suggest that within 2 months of the MVA, changes in gray matter volume have occurred in some brain regions of those suffering from PTSD. We believe the results of our study will provide useful insights into the neuropsychological mechanisms underlying PTSD.